Städtebauliche und sozioökonomische Implikationen neuer Mobilitätsformen Beiträge aus: Profilregion Mobilitätssysteme Karlsruhe - Schippl, Jens; Burghard, Uta; Baumgartner, Nora; Engel, Barbara; Kagerbauer, Martin; Szimba, Eckhard (KIT Scientific Publishing, 2022)
Many experts assume that urban mobility, and with it the urban environment, will change significantly in the future, partly due to new, digitally-supported mobility services. It is therefore important to understand how this change may look like and how it can be shaped. The papers in this volume aim to contribute to these questions from different perspectives. All of the papers were written in the project "Profilregion Mobilitätssysteme Karlsruhe".